System Usability Scale (SUS) As An Analysis Method For Official Website - Rahmawati, Berty Dwi; Wibowo, Astrid Wahyu Adventri; Fitrianingrum, Sabrina Nugrahani (Telematika, 2024)
Purpose: A company expands its product marketing by utilizing information systems. The quality of its information system influences product marketing expansion. Only a few companies have maximized the use of company websites. Usability testing on the company's official website determines the page's usability level.Design/methodology/approach: To address this issue, usability testing is conducted in this research using the System Usability Scale, whose testing involves page users. This usability level measurement technique has its characteristics. This method can obtain the level of usability precisely with user respondents from the page.Findings/result: Website testing was carried out with a structured and accurate SUS questionnaire using ten questions. The SUS score calculation was 80, considered excellent and acceptable to users.Originality/value/state of the art: PT Inka's Information System has never been analyzed during design or development. With this usability test, it is hoped that website users can find out the perceptions and problems experienced by users when interacting with the official website